Load deflection characteristics of HPC beam with GFRP rebars - Gowrisankar, S.; Dhinakaran, G.; Jeyasehar, C. Antony (Journal of Structural Engineering, 2024)
The use of Fiber Reinforced Polymer (FRP) is growing day by day in the recent time to eliminate the corrosion problem of steel and its higher strength to weight ratio. Though the cost of FRP rebars are around 30% more than steel, which is offset by comparing its life cycle cost reduction due to the ability of resistance of FRP rebar against corrosion. The fibers which are typically used as reinforcement are aramid, glass or carbon. Use of FRP rebar gained momentum and has number of advantages over conventional steel reinforcement. Hence, an attempt has been made in the present research work, to focus on the effect of high performance concrete beam reinforced with glass fiber reinforce polymer (GFRP) rebar. In the present work, two beams of size 125 x 200 x 2100 mm were considered. The grade of concrete used for the present work is M 40. One beam is reinforced with GFRP rebar and the other is with steel rebar. Two point loading test was carried out and the failure characteristics were studied. The plots showing load- defl ection curves at different sections of the beams were also developed. Thus the study provides a clear comparison of the performance of flexural member reinforced with GFRP rebar and steel rebar.